A Study of Fourth-Order Hankel Determinants for Starlike Functions Connected with the Sine Function. (24th April 2021) - Zhang, Hai-Yan; Tang, Huo
Abstract : In this paper, upper bounds for the fourth-order Hankel determinant H 4 1 for the function class S s ∗ associated with the sine function are given.